2022
DOI: 10.1128/spectrum.01972-22
|View full text |Cite
|
Sign up to set email alerts
|

Altered Fecal Microbiome and Correlations of the Metabolome with Plasma Metabolites in Dairy Cows with Left Displaced Abomasum

Abstract: LDA is a major contributor to economic losses in the dairy industry worldwide; however, the mechanisms associated with the metabolic changes in LDA remain unclear. Most previous studies have focused on the rumen microbiota in terms of understanding the contributors to the productivity and health of dairy cows; this study further sheds light on the relevance of the lower gut microbiota and its associated metabolites in mediating the development of LDA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Accumulating evidence suggests that the BCAAs, as gut microbiota-derived metabolites, can induce the insulin resistance by activating mammalian target of rapamycin complex 1 ( 29 , 61 ). We previously reported that the levels of isoleucine and leucine were markedly increased in dairy cows with left displaced abomasum events and were strongly correlated with the abundances of Akkermansia and Oscillospira in the feces ( 38 ). However, unlike leucine, an increase in isoleucine and valine levels adversely affects metabolic health by disturbing glucose homeostasis ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence suggests that the BCAAs, as gut microbiota-derived metabolites, can induce the insulin resistance by activating mammalian target of rapamycin complex 1 ( 29 , 61 ). We previously reported that the levels of isoleucine and leucine were markedly increased in dairy cows with left displaced abomasum events and were strongly correlated with the abundances of Akkermansia and Oscillospira in the feces ( 38 ). However, unlike leucine, an increase in isoleucine and valine levels adversely affects metabolic health by disturbing glucose homeostasis ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…After sample pre-treatment, fecal metabolome profiling was performed using ultra-high-performance liquid chromatography (UHPLC; Agilent 1290 Infinity II, Santa Clara, CA, USA) with tandem mass spectrometer (MS/MS; Triple Time-of-Flight 6600, AB SCIEX, Framingham, MA, USA). The pre-treatment conditions and equipment parameters are described in our previous report ( 38 ). The mass/charge ratio, retention time, and peak area of the metabolomic features were extracted using the XCMS ( https://xcmsonline.scripps.edu ) platform.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, iso-DCA has great potential as a warning system. Our previous study indicated that plasma TLCA was significantly and positively correlated with BHB and NEFA in dairy cows with a left-displaced stomach (hyperketotic status) ( Luo et al, 2022 ). Interestingly, most bile acids in the feces and plasma were UnconSBA.…”
Section: Discussionmentioning
confidence: 99%
“…UHPLC-Q-TOF MS was performed at Shanghai Applied Protein Technology Co., Ltd. The sample pretreatment, equipment parameters, and metabolite identification methods were the same as those used in our previous report ( Luo et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the amount of dietary nutrients in the digesta might also play a pivotal role in nutrient supply not only for the host but also for the microbiota community thus shaping the microbial composition. A recent study demonstrated that gastrointestinal microbiota dysbiosis is linked to the development of feed intake-related diseases such as left displaced abomasum (LDA) in dairy cows (17).…”
Section: Introductionmentioning
confidence: 99%